The Ninth Marcel Grossmann Meeting 2002
DOI: 10.1142/9789812777386_0176
|View full text |Cite
|
Sign up to set email alerts
|

Sn1987a: Temporal Models

Abstract: It is well known that carriers of astrophysical information are massless spinning particles. These carriers are photons, neutrinos and, expectedly, gravitons. All these particles are emitted during supernova events. Information carried by these particles characterize their sources, but such information are affected by the trajectories of the carriers. Recently, it is shown that these trajectories are spin dependent. Knowing these trajectories and the arrival times of such particles to the detectors, a spin dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Also, for more Refs. on the parameterized versions of these connections and their applications see [53][54][55][56][57][58][59][60][61]. However, the vielbein vector fields satisfy…”
Section: A Teleparallel Spacementioning
confidence: 99%
“…Also, for more Refs. on the parameterized versions of these connections and their applications see [53][54][55][56][57][58][59][60][61]. However, the vielbein vector fields satisfy…”
Section: A Teleparallel Spacementioning
confidence: 99%
“…Wanas et al [6] proposed the particle equation in the weak field limit of the gravitational field to be…”
Section: Weak Field Approximationmentioning
confidence: 99%
“…One of the authors of the present work [2] has generalized this set of equations and suggested that the torsion term represents a type of interaction between the torsion of the background gravitational field and the quantum spin of the moving particle. The generalized path equation mentioned above has been used , in its linearized form, to interpret [3] qualitatively and quantitatively the discrepancy in the COW-experiment. Also, the same equation has been used [4] to explain the time delay of massless spinning particles received from SN1987A.…”
Section: Introductionmentioning
confidence: 99%
“…The generalized path equation mentioned above has been used , in its linearized form, to interpret [3] qualitatively and quantitatively the discrepancy in the COW-experiment. Also, the same equation has been used [4] to explain the time delay of massless spinning particles received from SN1987A. It is to be considered that the generalized path equation can be used to describe trajectories of spinning particle in any gravity theory (including General Relativity) if it is written in the AP-geometry.…”
Section: Introductionmentioning
confidence: 99%